2015
DOI: 10.1093/jmammal/gyv151
|View full text |Cite
|
Sign up to set email alerts
|

Archaeology, biogeography, and mammalogy do not provide evidence for tarukas (Cervidae: Hippocamelus antisensis ) in Ecuador

Abstract: Knowing whether a species has been extirpated, or if it ever inhabited a specific geographic area, has direct importance for planning conservation activities. The taruka ( Hippocamelus antisensis ) is one of the largest Neotropical mammals; it is distributed in the central Andes, and there are published records of this species in Ecuador. Recently, missing museum specimens have cast doubts on the validity of these Ecuadorian records. Here, we examine whether the taruka ever inhabited Ecuador by analyzing multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…White-tailed deer inhabit all highland ecological zones (Emmons 1990: 162–163), while taruca is typically found in the puna at elevations ranging from 3500 to 5000 m asl (e.g., Barrio 2010, 2013; Flannery et al 1989: 19–20; Lynch 1980: 12–13; Pinto et al 2015). Based on these distributions, it is likely that the inhabitants of Canchas Uckro hunted within the immediate catchment of the site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…White-tailed deer inhabit all highland ecological zones (Emmons 1990: 162–163), while taruca is typically found in the puna at elevations ranging from 3500 to 5000 m asl (e.g., Barrio 2010, 2013; Flannery et al 1989: 19–20; Lynch 1980: 12–13; Pinto et al 2015). Based on these distributions, it is likely that the inhabitants of Canchas Uckro hunted within the immediate catchment of the site.…”
Section: Discussionmentioning
confidence: 99%
“…12-13; Pinto et al 2015). Based on these distributions, it is likely that the inhabitants of Canchas Uckro hunted within the immediate catchment of the site.…”
Section: Hunting Practicesmentioning
confidence: 99%
“…The nomenclature of geological units follows Schenk et al (1999). Geological units hotspot of endemism and biodiversity (Berry 1982, Borchsenius 1997, Ayers 1999, Weigend 2002, perhaps with a more recent geologic origin than the surrounding cordilleras (Mutke et al 2014), causing it to be identified as a possible dispersal barrier/limit for plants (Smith and Baum 2006, Cosacov et al 2009, Struwe et al 2009, Symmank et al 2011, Salariato et al 2016, insects (Acosta and Prat 2018), reptiles (Torres-Carvajal and Mafla-Endara 2013), mammals (Voss 2003, Marino et al 2011, Pinto et al 2015, Prado and Percequillo 2016, Diersing and Wilson 2017 and birds (Hazzi et al 2018 and glowing puffleg E. vestitus (Ecuador to Venezuela). On the other hand, the emerald-bellied puffleg E. alinae (central Peru to eastern Colombia) is at the base of the other subclade, which also includes E. luciani, the black-thighed puffleg E. derbyi (northern Ecuador to central Colombia), and the coppery-bellied puffleg E. cupreoventris (eastern Colombia to Venezuela).…”
Section: Discussionmentioning
confidence: 99%
“…Along the Andes there are three main patterns of allopatric distributions: (1) a latitudinal pattern is evidenced when a pair of sister species are distributed one to the north and the other to the south, e. g., Hippocamelus antisensis (north) vs. H. bisulcus (south), and Nasuella meridensis (north) vs. N. olivacea (south) (Helgen et al 2009;Pinto et al 2016); (2) a cross Andean pattern is evidenced when a pair of sister species are distributed with one in the eastern slopes and another in the western slopes of the Andes, e. g., Bassaricyon alleni (east) vs. B. medius (west) (Helgen et al 2013); and (3) altitudinal pattern is evidenced when one species is in higher elevations and its close relatives are in lower elevations, e. g., Bassaricyon neblina and Dactylomys peruanus vs. the rest of the species in their respective genera (Helgen et al 2013;Upham et al 2013). In this work, we highlight further possible examples of the cross Andean pattern of distributions: of the three species supposedly shared between the eastern and western slopes of the Andes, two (Chilomys instans and Akodon mollis) may represent multiple species.…”
Section: Discussionmentioning
confidence: 99%